Actinidia Berries in the Biotechnologicalproduction of Fermented Beverages (Bulletin of the Far Eastern Federal University. Economics and Management, 2025)
The article is devoted to the research and development of fermented berry soft drinks. The berries of actinidia kolomikta and argut, growing in the Far Eastern region, were used as raw materials. Actinidia berries contain vitamins, mineral biologically active substances, and are characterized  by  antioxidant  activity. To obtain fermented drinks, a decoction of actinidia berries and sugar syrup were used. To ferment the blend, kvass yeast Saccharomyces cerevisiae and dried actinidia berries were used. Non-alcoholic fermented drinks based on actinidia berries had a pleasant sweet and sour taste and a light specific aroma. The dry matter content is 7.9-8.1%, acidity — 6.3-6.5 units, vitamin C — 25.2-26.1 mg/100 cm3.